Effects of capture-related stress and pre-freezing holding in refrigerated sea water (RSW) on the muscle quality and storage stability of Atlantic mackerel (Scomber scombrus) during subsequent frozen storage. (30th March 2023) - Anders, Neil; Breen, Michael; Skåra, Torstein; Roth, Bjørn; Sone, Izumi
Highlights: Interactive effects on crowding stress, refrigerated seawater holding and frozen storage. Quality metrics with K-value, WHC, cathepsin activity, lipid oxidation, texture, pH, colour. Frozen storage with the largest and most consistent direct effects on muscle quality. Crowding stress affected quality through interactions with frozen storage and RSW treatment. Further studies with larger sample sizes necessary to elucidate complex effects and interactions. Abstract: Crowded (stressed) and unstressed Atlantic mackerel with or without pre-freezing holding in refrigerated sea water (RSW) were stored at −19 °C for ∼12 months and analysed for nucleotide degradation (K value), muscle pH, water holding capacity (WHC), fillet firmness, cathepsin B/L like activity, lipid oxidation and fillet colour. The frozen storage showed the largest and most consistent direct effects on the quality metrics leading to increased lipid oxidation, discolouration (yellowing) and reduction on WHC and cathepsin activity. RSW treatment promoted nucleotide degradation and reduced WHC and fillet firmness in interaction with frozen storage and affected fillet colour lightness and saturation. Although showing only marginal main effects, crowding stress modified WHC, cathepsin activity and fillet firmness and colour through significant interactions with the frozen storage and RSW treatment. Further studies with larger sample sizes would be needed to elucidate their complex effects and interactions on the quality and storage stability of mackerel.